2021
DOI: 10.1108/jkm-06-2021-0453
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital, knowledge management and competitive advantage: a resource orchestration perspective

Abstract: Purpose This study aims to examine the influence of intellectual capital and knowledge management on competitive advantage with the mediation role of innovativeness in the Pakistan manufacturing industry. Moreover, differentiation strategy is used as a moderator between innovativeness and competitive advantage. Design/methodology/approach The data was collected from 387 manufacturing firms in Pakistan through questionnaires. Purposive random sampling was used to collect data. The partial least square structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 119 publications
4
116
0
4
Order By: Relevance
“…A total of 39,158 constructions and 47,698 manufacturing SMEs are working in Malaysia. This consists only of constructs established by previous researchers and that also measured the variables according to five‐Likert scales (Elrehail et al, 2021; Khan et al, 2019; Rehman, Ashfaq, et al, 2021; Rehman, Bresciani, et al, 2021; Rehman, Elrehail, et al, 2021; Rehman, Samad, et al, 2021; Sun et al, 2022). For data collection, researchers used a simple random sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 39,158 constructions and 47,698 manufacturing SMEs are working in Malaysia. This consists only of constructs established by previous researchers and that also measured the variables according to five‐Likert scales (Elrehail et al, 2021; Khan et al, 2019; Rehman, Ashfaq, et al, 2021; Rehman, Bresciani, et al, 2021; Rehman, Elrehail, et al, 2021; Rehman, Samad, et al, 2021; Sun et al, 2022). For data collection, researchers used a simple random sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…, 2021; Khan et al. , 2019; Rehman et al ., 2020, 2021a, b, c). The researchers collect data from only that person who has the online experience to book a hotel.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 60 questionnaires were filled from every hotel. Various researchers used the five-point Likert scale to measure variables (Bhatti and Rehman, 2020;Elrehail et al, 2021;Khan et al, 2019;Rehman et al, 2020Rehman et al, , 2021a. The researchers collect data from only that person who has the online experience to book a hotel.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Resource-based theory suggested that enterprises have different tangible and intangible resources, and when a particular resource is valuable, scarce, irreproducible, and difficult to replace, it can give the enterprise a long-lasting competitive advantage [21][22][23]. Data assets, on the other hand, as unique digital resources that many enterprises acquire through their business activities, have an important place in the creation of enterprise value [24].…”
Section: Methodsmentioning
confidence: 99%